Living organisms and sedimentary remains from high mountain lakes in the Alps - Marchetto, Aldo (2021)
We publish a data set of environmental and biological data collected in 2000 during the ice-free period in high mountain lakes mainly located above the local timberline in the Alps, in Italy, Switzerland and Austria. Environmental data include coordinates, geographical attributes and detailed information on vegetation, bedrock and land use in lake catchments. Chemical analyses of a sample for each lake collected at the lake surface in summer 2000 are also reported. Biological data include phytoplankton, zooplankton, macroinvertebrates, benthic diatoms. Diatoms, cladoceran and chironomids remains and algal and bacterial pigments were also analysed in lake sediments.